IDENTIFIKASI KELAYAKAN USAHA BUMDES PADA ASPEK EKONOMI DAN SOSIAL (Studi Kasus BUMDes Sekar Pandan Desa Karangpandan Rejoso Pasuruan) - Bambang Sutikno; Yufenti Oktafiah (Jurnal Inovasi Penelitian, 2023)
The economy of the village community is an important factor in assessing the success of village development according to Law Number 6 of 2014 concerning villages article 1 number 6 states that village-owned enterprises, hereinafter referred to as BUMDes, are business entities whose capital is wholly or partly owned by the village through direct participation originating from village assets separated to manage assets, services and other businesses for the maximum welfare of the village community. This article states that the management of BUMDes is carried out entirely by village communities from village by village and for village communities in an effort to strengthen their economy and is formed based on the needs and economic potential of village resources. It is hoped that the establishment of BUMDes is not only oriented towards institutional profits but also prioritizes improving the economy and social life of village communities. This study aims to assess the feasibility of implementing village-owned enterprise (BUMDes) business activities from economic and social aspects. This research was conducted using descriptive qualitative methods with data collection techniques through interviews, documentation, observation and literature review with subjects as key research informants, namely BUMDes managers, village heads and one BUMDes service user. Measurement assessment analysis uses aspects of the feasibility study indicators. The results of the study show that the existence of Sekar Pandan BUMDes in Karangpandan Rejoso Pasuruan Village in terms of vision, mission and objectives is currently still not appropriate, so that its positive role in improving the economy and social cannot be directed by the village community in general, while from a business feasibility assessment it is still necessary to increase the management capacity of the community with assistance and guidance from related agencies on a cross-sectoral basis